Pemikiran Ekonomi Islam Imam Al-Ghazali Tentang Uang Dalam Perspektif Maslahah Mursalah - Huril Aini (Universitas Islam Lamongan, 2018)
Economic activity is defined as inseparable thing in life. The process that occurs in terms of exchange with a particular agreement creates a system which we then call the economic transactions. The transaction is nothing but an attempt to make ends meet. In this case, the government will supervise the activities. Individual actions in the economy in particular and action in general, depends on the mind and worldview of the individual. Therefore, Islam as a universal religion has regulated and provided the right pattern of action in life, socially, culturally and economically. The writing will try to answer the question: how the Islamic economic thought of Imam al-Ghazali on money in the context of mashlahah mursalah. The research is literature research, which examines the sources of books, books, scientific journals, articles and other forms of material or commonly related to the discussion of this paper. The data have been collected from many sources, analyzed using content analysis method, namely research technique to make replicable inference and valid data with respect to context. The description is presented in descriptive or narrative form the data already collected is analyzed in accordance with historical events or facts, especially the detailed description of the activity, attitude, behavior and position of Imam al-Ghazali in historical events. In addition, data analysis is presented in an inductive form on data already collected or evidence analyzed, compiled or abstracted based on existing sources (primary data and secondary data). The results showed that to build a good economy and smoothly should be able to run economic activities based on Islamic law by implementing the concept of mashlahah mursalah, including in managing finances well according to the needs of the community and conduct muamalah activities in accordance with the existing ethics. Islamic economy according to Imam al-Ghazali in its achievement must promote the public good. It implements the concept of maslahah mursalah with the maintenance of the five basic objectives (maqashid shari’ah). While in carrying out economic activities, the government must intervene, especially when there are problems in the community. Economic goals should not be concerned only one side of life, but must be balanced between the world and the hereafter. Keywords: Imam al-Ghazali, Money, Maslahah Mursalah